BARA MERAPU SEBAGAI KEPERCAYAAN ASLI ORANG SUMBA (Perspektif Pelayanan Hak Sipil dan Ancaman Kepunahan) - Servulus Bobo Riti (Harmoni, 2015)
This research was conducted in Sumba Barat Daya Regency, East Nusa Tenggara Province. The aim is to discover the fulfillment of the civil right services of Bara Marapu belief as ruled in Undang-undang Nomor 23 Tahun 2006 regarding to Adminduk. The research is undertaken from April to August 2013 and employs qualitative approach. The result shows that the adherents of Bara Marapu have been decreasing because of national policy that obliges all students to choose one of the official religions determined in Indonesia. Mostly they choose Protestantism and Catholicism that are already developed in Sumba. The result also shows that the adherents of Bara Marapu have civil rights such as having birth certificate, identity card, and health and educational services. Bara Marapu belief does not have a written documentation. It is suggested to the government to document it as a local belief.